Pengendalian Manajemen Sebagai Upaya Mengoptimalkan Kinerja Keuangan - Amalina, Nur; Erikawati, Civi; Haziroh, Awanis Linati (Jurnal Manajerial, 2024)
Background – The debt phenomenon is very crucial in the company. Many entrepreneurs go bankrupt or fail to pay due to debts owned by the company so that debt has a big pressure on generating company profits. Aim – This research is to analyze the influence of corporate governance on financial performance and external pressure as mediating variables. Design / methodology / approach – The cumulative method used to describe relationships in research and the analysis tool is Eviews.10 software. The sample used was 720 observation data from 144 financial sector companies for five years (2018-2022). Findings – This shows that the board has a significant negative impact on external pressure. Independent directors and commissioners have a significant positive influence on external pressure. The board of directors has a significant positive influence on financial performance. Board independence has no effect on financial performance. Board and external pressures have a material negative impact on financial performance. External pressure indirectly has a negative and significant influence on financial performance among independent directors and commissioners. We also provide active and authoritative mediation between the board of directors and financial performance. Conclusion – This needs to be taken into consideration that external pressure has a strong impact on independent directors and the board of commissioners so that the resulting performance will decrease, while the board of directors will have a strong impact on improving performance because the board of directors is able to control the pressure that arises from stakeholders. Research implication – For manufacturing companies, they will be able to see which ones can provide an increase in company profits so that they will be able to maximize corporate governance in managing the company's finances. Limitations – This research only uses one sector, namely manufacturing companies. This research needs to be expanded to different sectors.